2010
DOI: 10.1509/jmkr.47.5.945
|View full text |Cite
|
Sign up to set email alerts
|

Power Distance Belief and Impulsive Buying

Abstract: The authors propose that power distance belief (PDB) (i.e., accepting and expecting power disparity) influences impulsive buying beyond other related cultural dimensions, such as individualism–collectivism. This research supports an associative account that links PDB and impulsive buying as a manifestation of self-control, such that those with high PDB display less impulsive buying. Furthermore, this effect manifests for vice products but not for virtue products. The authors also find that restraint from tempt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
207
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(215 citation statements)
references
References 31 publications
3
207
5
Order By: Relevance
“…Elevated power, for instance, is associated with disinhibited behavior that is uninfluenced by social norms . For example, Zhang et al (2010) explain how more consumers with a greater sense of empowerment demonstrate uninhibited behavior like impulsive buying of products for immediate gratification (that is, vice products). Another form of uninhibited behavior characteristic of empowered consumers is protesting (Ward and Ostrom, 2006).…”
Section: Consumer Brand Empowerment and Desired Brand Experiencementioning
confidence: 99%
“…Elevated power, for instance, is associated with disinhibited behavior that is uninfluenced by social norms . For example, Zhang et al (2010) explain how more consumers with a greater sense of empowerment demonstrate uninhibited behavior like impulsive buying of products for immediate gratification (that is, vice products). Another form of uninhibited behavior characteristic of empowered consumers is protesting (Ward and Ostrom, 2006).…”
Section: Consumer Brand Empowerment and Desired Brand Experiencementioning
confidence: 99%
“…For the most part, these studies focused almost exclusively on U.S. samples (except for Kacen and Lee 2002;Mai et al 2003;Zhang, Winterich, and Mittal 2010 for impulsive buying behavior; Baker et al 2013;and Shoham and Brencic 2003 for compulsive buying behavior); centered on examining the associations between consumer personality traits and impulsive or compulsive behaviors (e.g., Faber and O'Guinn 1992;O'Guinn and Faber 1989;Scherhorn et al, 1990;Youn and Faber 2000). Additionally, with the increasing globalization of the marketplace, scholars have long recognized the importance of cultural characteristics in the context of consumer behavior (Maheswaran and Shavitt 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, research on the effect of cultural dimensions on impulsive and compulsive buying behavior is limited. Studies focused exclusively on impulsive buying behavior, examining either individualism-collectivism (e.g., Kacen and Lee 2002;Mai et al 2003) or power distance (Zhang et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Sneath, Lacey and Kennett-Hansel (2009) examined that victim of disaster found making impulse buying decision. Other study by Zhang et al (2010) identified that distance of power belief is found to be affected by the consumer impulsive purchasing decision. (2002) claimed that the uses of surprise in-store promotion, such as coupons impacted on the consumer impulsive buying decision making.…”
Section: Theoretical and Empirical Perspective Of Impulse Buying Behamentioning
confidence: 97%